In vivo dosimetry and shielding disk alignment verification by EBT3 GAFCHROMIC film in breast IOERT treatment. (8th January 2014) - Severgnini, Mara; de Denaro, Mario; Bortul, Marina; Vidali, Cristiana; Beorchia, Aulo
Abstract : Intraoperative electron radiation therapy (IOERT) cannot usually benefit, as conventional external radiotherapy, from software systems of treatment planning based on computed tomography and from common dose verify procedures. For this reason, in vivo film dosimetry (IVFD) proves to be an effective methodology to evaluate the actual radiation dose delivered to the target. A practical method for IVFD during breast IOERT was carried out to improve information on the dose actually delivered to the tumor target and on the alignment of the shielding disk with respect to the electron beam. Two EBT3 GAFCHROMIC films have been positioned on the two sides of the shielding disk in order to obtain the dose maps at the target and beyond the disk. Moreover the postprocessing analysis of the dose distribution measured on the films provides a quantitative estimate of the misalignment between the collimator and the disk. EBT3 radiochromic films have been demonstrated to be suitable dosimeters for IVD due to their linear dose‐optical density response in a narrow range around the prescribed dose, as well as their capability to be fixed to the shielding disk without giving any distortion in the dose distribution. Off‐line analysis of the radiochromic film allowed absolute dose measurements and this is indeed a very important verification of the correct exposure to the target organ, as well as an estimate of the dose to the healthy tissue underlying the shielding. These dose maps allow surgeons and radiation oncologists to take advantage of qualitative and quantitative feedback for setting more accurate treatment strategies and further optimized procedures. The proper alignment using elastic bands has improved the absolute dose accuracy and the collimator disk alignment by more than 50%. PACS number: 87.55.kh